Biopower in the age of the pandemic: the politics of COVID-19 in Denmark. Issue 5 (20th October 2022) - Triantafillou, Peter
ABSTRACT: The exceptional forms of state power mobilized under COVID-19 have attracted scholarly attraction and created important insights on the pandemic politics. However, it seems that the current understanding tends to regard the states' responses as a zero-sum game between two powers only, a game in which liberal rule in varying degrees is traded for raw sovereign power. Inspired by the notion of biopower, this article aims to provide a more nuanced account of the various powers invoked to handle the pandemic. Based on the case of Denmark, it is argued that three forms of power were mobilized: sovereignty, discipline and security mechanisms. Yet, indirect security mechanisms informed by epidemiological knowledge and modelling have played a far more comprehensive role than the two other power mechanisms. In a complex interaction with epidemiological expertize, liberal governmentalities limited the mobilization of sovereignty and discipline and, instead, tended to endorse indirect security mechanisms.